2011
DOI: 10.1177/0022185610397143
|View full text |Cite
|
Sign up to set email alerts
|

Research Note: Workplace Child Care and Elder Care Programs and Employee Retention

Abstract: Using Statistics Canada's Workplace and Employee Survey (WES) data for 2003 and 2004, this research note addresses an important component of labour market retention by investigating whether the presence of workplace child care and elder care programs influences employees' decision to quit. The key findings are as follows: (a) workplace elder care support is almost non-existent in Canada; (b) employees are more likely to remain with an organization that offers workplace child care support programs; and (c) thos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 3 publications
1
1
0
1
Order By: Relevance
“…(2008) found that women aged in their 50s who took up a role caring for an ill, frail or disabled person had lower rates of labour force participation than other mid-life Australian women. International studies that have focused on mid-life women have reached similar conclusions (Bolin et al., 2008; Hank, 2004; Pavalko and Artis, 1997; Spiess and Schneider, 2003; Wakabayashi and Donato, 2005), corroborating the results of investigations into the employment effects of informal care across all demographic groups (Carmichael and Charles, 1998; Henz, 2004; Larsen, 2010; Leigh, 2010; McLanahan and Monson, 1990; Mann et al., 2011). However, the employment impacts of care roles have typically been found to be greater in a cross-sectional than longitudinal perspective, 3 and at least one study of the issue (by Wolf and Soldo, 1994) found no effect of informal care on employment or hours worked.…”
Section: Introductionsupporting
confidence: 52%
See 1 more Smart Citation
“…(2008) found that women aged in their 50s who took up a role caring for an ill, frail or disabled person had lower rates of labour force participation than other mid-life Australian women. International studies that have focused on mid-life women have reached similar conclusions (Bolin et al., 2008; Hank, 2004; Pavalko and Artis, 1997; Spiess and Schneider, 2003; Wakabayashi and Donato, 2005), corroborating the results of investigations into the employment effects of informal care across all demographic groups (Carmichael and Charles, 1998; Henz, 2004; Larsen, 2010; Leigh, 2010; McLanahan and Monson, 1990; Mann et al., 2011). However, the employment impacts of care roles have typically been found to be greater in a cross-sectional than longitudinal perspective, 3 and at least one study of the issue (by Wolf and Soldo, 1994) found no effect of informal care on employment or hours worked.…”
Section: Introductionsupporting
confidence: 52%
“…International studies that have focused on mid-life women have reach similar conclusions (Pavalko and Artis 1997; Spiess and Schneider 2003;Hank 2004;Wakabayashi and Donato 2005;Bolin, Lindgren et al 2008), corroborating the results of investigations into the employment effects of informal care across all demographic groups. (McLanahan and Monson 1990;Carmichael and Charles 1998;Henz 2004;Leigh 2010;Larsen 2010;Mann, Cooke et al 2011) However, the employment impacts of care roles have typically been found to be greater in the cross-section than in a longitudinal perspective iii , and at least one study of the issue (by Wolf and Soldo (1994)) found no effect of informal care on employment or hours worked.…”
Section: Employment Retention Women Informal Care Ill-health Workmentioning
confidence: 99%
“…Качество жизни (благополучие) членов организации и его показатель -развитие человеческого потенциала -в современных исследованиях рассматриваются в разных аспектах. Это, например, социальная поддержка сотрудников в воспитании детей [1], гендерное равенство [2], культурное разнообразие в организации [3], организационно-психологические аспекты работы сотрудников [4], использование методов искусства в организации условий и процессов предприятия [5].…”
unclassified